Producing the archival body - Lee, Jamie A. (Jamie Ann), author.
1 online resource
Keywords: "Producing the Archival Body draws on theoretical and practical research conducted within US and Canadian archives, along with critical and cultural theory, to examine the everyday lived experiences of archivists and records creators that are often overlooked during archival and media production. Expanding on the author's previous work, which engaged archival and queer theories to develop the Queer/ed Archival Methodology that intervenes in traditional archival practices, the book invites readers interested in humanistic inquiry to re-consider how archives are defined, understood, deployed, and accessed to produce subjects. Arguing that archives and bodies are mutually constitutive and developing a keen focus on the body and embodiment alongside archival theory, the author introduces new understandings of archival bodies. Contributing to recent disciplinary moves that offer a more transdisciplinary emphasis, Lee interrogates how power circulates and is deployed in archival contexts in order to build critical understandings of how deeply archives influence and shape the production of knowledges and human subjectivities. Producing the Archival Body will be essential reading for academics and students engaged in the study of archival studies, library and information science, gender and women's studies, anthropology, history, digital humanities, and media studies. It should also be of great interest to practitioners working in and with archives"--